Peer Counselors as Agents of Inclusion: A Mixed-Methods Study on Multicultural Competence and Counseling Effectiveness in Higher Education - Asti Haryati; I Wayan Darmayana; Rita Sinthia; Umi Umayyah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study explores the effectiveness of peer counselors in delivering multicultural-based counseling services within a higher education context in Indonesia. Using a convergent mixed-methods design, data were collected from 33 university students through questionnaires and semi-structured interviews with nine participants. Quantitative analysis revealed a strong positive correlation between peer counselor effectiveness and counseling outcomes (r = 0.666, p < 0.01), indicating that counselor effectiveness explains 44.4% of the variance in counseling success. The qualitative findings further identified four interrelated themes shaping effective multicultural peer counseling: counselor–client relationship, communication skills, service quality, and cultural sensitivity. Integration of both data sets demonstrated that peer counselors act not only as providers of emotional support but also as agents of inclusion, fostering trust, empathy, and intercultural understanding among students. The findings emphasize that multicultural competence particularly empathy and cultural awareness is essential for enhancing the quality and inclusiveness of peer counseling. This study contributes to the growing literature on multicultural counseling by providing empirical evidence from a non-Western, multicultural context, underscoring the importance of structured training and institutional support to sustain peer counseling as a preventive and promotive model for student mental health in higher education.